Increase Noise Hazard on Incident of Occupational Diseases in Agroindustrial Area - Kurniyawan, Enggal Hadi; Isyroq, Haidar Fadhilatin; Rifa’i, Achmad; Rusmawati, Adinda Athalia; Ramadhan, Ibadillah Hilmy Dzulfiqar; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad (International Journal of Midwifery and Health Sciences, 2023)
Background: The sound generated by a tractor engine is one of the causes of ear disorders. This is usually experienced by people who live in agro-industrial areas, especially those who work as farm laborers, especially when planting and harvesting. Most people spend their free time in the fields, so they indirectly listen to the sound produced by the tool. Purpose: The literature review study aims to discover the increase of noise hazards on incidents of occupational diseases in agro-industrial areas. Methods: The method used in the preparation of this Literature Review was obtained from 3 database sources, namely Google Scholar, ScienceDirect, and Pubmed, which was published from 2018 to 2021 using Indonesian keywords, namely "Noise" OR "Agro-industry" OR "Hearing Impaired" OR "Occupational Health Risks". After searching for journal articles using the Google Scholar search engine, according to the keywords that have been determined. Literature analysis took ten journal articles published in 2018-2023, 5 articles discussing noise, two articles discussing hearing loss, two articles discussing occupational health risks, and 1 article discussing agro-industry. Results: From this study, it can be concluded that the presence of noise intensity that has exceeded the threshold value (85 dB) can increase the risk of increased blood pressure of workers, leading to workplace hypertension. In addition, noise can also cause stress because it is one type of stressor in the workplace. Conclusion: It is crucial to plan various ear plug measures to reduce noise exposure in the workplace. The nurse's suggestion is to build public awareness regarding the importance of protecting the ears from noise, one of which is using ear plugs. The purpose of the earplug is to protect and reduce the level of noise that enters the ear.